Pengaruh Profitabilitas dan Leverage Terhadap Manajemen Laba pada Perusahaan Manufaktur Sebagai Kajian Literatur - Febrian San Fernando; Mardani Supranata (Jurnal Akuntansi Manajerial, 2026)
This study aims to comprehensively analyze the effect of profitability and leverage on earnings management through a Systematic Literature Review (SLR) approach. This review was conducted by identifying, evaluating, and synthesizing empirical findings from various scientific articles published between 2015 and 2025, both in accredited national journals and reputable international journals. The literature selection process was carried out systematically through the stages of formulating research questions, determining inclusion and exclusion criteria, searching scientific databases, and conducting thematic analysis of relevant research results. The results of the study show inconsistencies in empirical findings regarding the relationship between profitability and leverage on earnings management. Some studies found that profitability and leverage have a positive effect on earnings management practices, while other studies show a negative or insignificant effect. These differences in results are influenced by industry characteristics, corporate governance mechanisms, and the approach used to measure earnings management. Thus, this study provides a comprehensive mapping of research gaps and recommends directions for further empirical studies that are more contextual and methodological.